DRIVE RECORDER, DISPLAY DEVICE FOR DRIVE RECORDER, AND PROGRAM - HATTORI TETSUYA; IWASA KANAME; YORIFUJI YUUKI; TAKAHASHI KEIZO; NAKAMURA HIROKO; SHIMIZU YUKI; OSHIMA HIROAKI (2024)
To provide a drive recorder having a large photographable range and a small dead angle, a display device for the drive recorder, and a program.SOLUTION: A drive recorder 10 comprises: a body case 13 for mounting a control unit and sound recording means; and a first camera 26 and a second camera 27 for photographing a range of a half-celestial sphere or more. The two cameras are mounted in a casing 25 so as to photograph opposite directions respectively. In a state where the body case 13 in which the control unit and the like are mounted is adhered and fixed on a windshield, the dashboard and a pillar of the vehicle appear in the peripheries of images photographed respectively by the two cameras.SELECTED DRAWING: Figure 3 【課題】撮影できる範囲が広く、死角が少ないドライブレコーダー、ドライブレコーダー用表示装置及びプログラムを提供する。【解決手段】ドライブレコーダ１０は、制御部と録音手段を実装する本体ケース１３を備え、半天球以上の範囲を撮影する第一カメラ２６と第二カメラ２７を備える。２つのカメラは、それぞれ反対方向を撮影するように筐体２５内に実装する。制御部等を実装する本体ケース１３をフロントガラスに貼付けて固定した状態では、２つのカメラがそれぞれ撮影する映像の周縁に、車両のダッシュボードとピラーが映るようにする。【選択図】図３